'A reformed Buddhism […] would help in the distant future to bring about a mutual understanding': Friedrich Max Müller's Conceptions of Religious Reform, Ecumenical Dialogue and World Peace1. (1st September 2016) - Dedryvère, Laurent; Prévost, Stéphanie
Abstract : The notion of religious reform pervades Friedrich Max Müller's work from the very beginning. Originally rooted in a Christian context and informed by contemporary theological controversies in Germany and in England, his conception of 'reform' is expanded into a hermeneutic tool to interpret the general history of religion(s). As a scholar involved in contemporary public debates, Müller considered reform as an ethical requirement, likely to promote a spiritual regeneration of colonial Asia in particular, and to foster the cause of world peace. Although he never challenged the primacy of Christianity, Müller wished for its purification from dogmatism and ritualism. Only a simultaneous reform of all major religions would allow for their convergence in an all-embracing Christianity.